2021
DOI: 10.1002/asi.24497
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between misinformation and outrage trolling tactics on two Yahoo! Answers categories

Abstract: As the prevalence of online misinformation grows increasingly apparent, our need to understand its spread becomes more essential. Trolling, in particular, may aggravate the spread of misinformation online. While many studies have investigated the negative impact of trolling and misinformation on social media, less attention has been devoted to the relationships between the two and their manifestation on social question and answer (SQA) sites. We examine the extent of and relationships between trolling and misi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Using data from Reddit, our study supports research on Yahoo! Answers communities that found that questions and answers in politics attract more trolling than other topics (Fichman & Vaughn, 2020; Gammon, 2014; Guy & Shapira, 2018). Yet, while Guy and Shapira (2018) found that health topics were as likely to attract trolling as entertainment topics on Yahoo!…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using data from Reddit, our study supports research on Yahoo! Answers communities that found that questions and answers in politics attract more trolling than other topics (Fichman & Vaughn, 2020; Gammon, 2014; Guy & Shapira, 2018). Yet, while Guy and Shapira (2018) found that health topics were as likely to attract trolling as entertainment topics on Yahoo!…”
Section: Discussionmentioning
confidence: 99%
“…These differences might be a result of differences across platforms, but it is also possible that the health subreddits have been monitored more closely during COVID19 global pandemic, for the fear of the spread of misinformation. Efforts to reduce misinformation may have played a critical role in combatting trolling as well, because misinformation and trolling impact each other (Fichman & Vaughn, 2020). Future research may examine trolling on health topics across platforms and over time.…”
Section: Discussionmentioning
confidence: 99%
“…For data analysis, we used four trolling tactics to code the comments, based on work that identified outrage tactics in online political discourse (Sobieraj & Berry, 2011), which we examined considering the data (Table 2). We felt that using these outrage tactics to code our data is appropriate because Sobieraj and Berry (2011) work examined incivility in political discourse based on data from online blogs, talk radio, and cable news; these trolling tactics have also been utilized in the analysis of online trolling (e.g., Fichman & Dainas, 2018; Fichman & Vaughn, 2021; Sanfilippo et al, 2018). The codebook was finalized after an iterative process of coding and discussion between the two coders, as codes were combined, eliminated, added, and redefined.…”
Section: Methodsmentioning
confidence: 99%
“…The FNI-related factors affecting the acceptance and spread of FNI are information cues, news type, credibility of news sources and the presentation format of news. News containing trolling (Fichman and Vaughn, 2021) and persuasive and uncertain words (Zhou et al, 2021a), and that accompanying a high number of Facebook "likes" (Ali et al, 2022) are more likely to be disseminated. The veracity of headlines has little effect on sharing intention despite the fact that it has a considerable effect on judgements of accuracy (Pennycook et al, 2021).…”
Section: Input Of Fnimentioning
confidence: 99%
“…The FNI-related factors affecting the acceptance and spread of FNI are information cues, news type, credibility of news sources and the presentation format of news. News containing trolling (Fichman and Vaughn, 2021) and persuasive and uncertain words (Zhou et al. , 2021a), and that accompanying a high number of Facebook “likes” (Ali et al.…”
Section: Literature Analysismentioning
confidence: 99%